KOMUNIKASI DAKWAH DALAM TINAJAUAN SOSIOLOGI KOMUNIKASI - ANDRIAN, BOB (TASAMUH, 2020)
The scientific clusters in the field of communication studies and Da'wah experienced a significant development of scientific studies, especially in the study clusters of da'wah and practical communication. Many assumptions lead to scientific arguments, including how the two disciplines combine in the view of Sociology of Communication. Answering these questions, the discussion of this study with filed research, descriptively, through the sociology approach. According to the practice view of the sociology of communication, the scopes focus of study, namely, the interaction process, its objectives and functions, the object of study, and its role in the social sphere. Theoretically and the concept both have a basis point of view that seems to be in opposing directions, but when examined for the Sociology of Communication, they both have the same direction and goal, that is, both are a process of interaction between one party and another that takes place. The community, both formal and informal with a specific purpose.